P2G 기술을 활용한 배전계통 신뢰도 향상에 관한 연구 - 이학주(Hak-Ju Lee); 손영건(Yeoung-Geoun Son); 오병찬(Byeoung-Chan Oh); 김성열(Sung-Yul Kim) (전기학회 논문지 P권, 69(2), 2020)
The importance of electricity use and dependence on electricity are increasing as the number of domestic and foreign electric facilities increases due to the development of science and technology. For customers receiving electricity, even if the number of power outages per year is not high, the damage and impact on it cannot be ignored. From this point of view, the reliability of the power system is an important issue that cannot be taken lightly. In this paper, we proposed a method to increase the reliability in the power system by using P2G technology that uses gas and electricity together to show better reliability in the existing power system KCI Citation Count: 0